Changes in Mean Arterial and Blood Pressure in Using Nicardipine in Hypertensive Crisis Patients at the Hajj General Hospital Surabaya from August to December 2021 - Selly Septi Fandinata; Rizky Darmawan; Ninik Mas Ulfa; Deddy Aryanda Putra (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Hypertension crisis is one of the most common disease problems; it will cause complications and death. Therapeutic management guidelines that the calcium channel blocker group, one of which is nicardipine, can increase the achievement of goals in mean arterial pressure (MAP) in preventing the progression of organ damage. This study aimed to evaluate the use of nicardipine therapy on the MAP and blood pressure (BP) in patients with hypertension crisis. The research design was cross-sectional with statistical analysis—retrospective data collection at Hajj General Hospital Surabaya for August to December 2021. The number of samples in this study matched the inclusion criteria; 20 patients were obtained, 16 with a diagnosis of hypertension emergency, and four with hypertension urgency who received single or combined intravenous nicardipine therapy <0.005 with an average BP decrease of pre 20.375±31.492/103.50±10.400 mmHg and post 121.34±14.364/81.80±11.186 so that intravenous nicardipine therapy was significant in reducing systolic and diastolic BP. In the profile of the MAP value statistically using the paired T-test, it was found that the P-value was 0.000 < 0.005 with a decrease in the MAP pre-value of 135.028±13.8857 mmHg and post 93.650±8.9499 mmHg, showing a reduction in MAP as expected. In conclusion, using nicardipine intravenously at a 5 mg/hour dose has shown an optimal decrease in BP and MAP in hypertensive emergency and urgency patients.